2006
DOI: 10.1016/j.jeem.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conservation in agriculture: Land retirement vs. changing practices on working land

Abstract: The study develops a conceptual framework for analyzing the allocation of conservation funds via selectively offering incentive payments to farmers for enrolling in one of two mutually exclusive agricultural conservation programs: retiring land from production or changing farming practices on land that remains in production. We investigate how the existence of a pre-fixed budget allocation between the programs affects the amounts of environmental benefits obtainable under alternative policy implementation sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 13 publications
(5 reference statements)
2
32
0
2
Order By: Relevance
“…The difference in size is also reflected in the total amount of carbon sequestered and erosion and nitrogen runoff reduced. This is consistent with the findings of Feng et al (2004) who found that for carbon sequestration, conservation tillage is significantly more cost-effective than is land retirement in Iowa. Note that "CRP with CT" is something of a win-win situation in the sense that both the transfer rate and the environmental benefits are higher than in the other two scenarios.…”
Section: Environmental Indicatorssupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in size is also reflected in the total amount of carbon sequestered and erosion and nitrogen runoff reduced. This is consistent with the findings of Feng et al (2004) who found that for carbon sequestration, conservation tillage is significantly more cost-effective than is land retirement in Iowa. Note that "CRP with CT" is something of a win-win situation in the sense that both the transfer rate and the environmental benefits are higher than in the other two scenarios.…”
Section: Environmental Indicatorssupporting
confidence: 91%
“…Since the 1997 NRI does not have information on the use of conservation tillage, the econometric models are first estimated using the 1992 NRI and then calibrated to the 1997 sub-watershed-average conservation tillage adoption rates provided by the Conservation Technology Information Center (CTIC 2000), using the procedure described in Feng et al 2004. We use the calibrated models to predict 1997 NRI tillage baseline, that is, which points use conservation as opposed to conventional tillage, as well as to estimate pointspecific subsidies needed for the adoption of conservation tillage for the data points that are predicted to currently employ conventional tillage.…”
Section: Costs Of Conservation Practicesmentioning
confidence: 99%
“…A promising alternative approach involves the incorporation of relatively small amounts of perennial cover in strategic locations within agricultural landscapes (Asbjornsen et al in review). Over the past decade, policies have targeted such conservation practices by, for example, promoting the establishment of riparian buffer systems, and grass waterways (Feng et al, 2004). However, achieving the most appropriate balance for maximizing hydrologic functions proportional to the amount of land removed from production will require a better understanding on the influence of spatial extent, position, and type of perennial vegetation within a watershed (Dosskey et al, 2002;Blanco-Canqui et al, 2006), about which little empirical field data exist.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous government programs around the globe have been implemented to control or influence public and private land uses (Langpap and Wu, 2004;Crepin, 2005;Feng et al, 2006;Clement and Amezaga, 2009;Henger and Bizer, 2010;Bullock and King, 2011). In the United States, for instance, federal policies such as the National Environmental Policy Act, Farm Bills, the Endangered Species Act, and the Clean Water Act all place regulatory requirements on land use practices.…”
Section: Introductionmentioning
confidence: 99%